Crowding, Race, and Ethnicity: A Case Study at Onondaga Cave State Park. Issue 1 (April 2019) - Lee, KangJae Jerry; Morgan, Mark; Shim, Hyojeong
This study investigated crowding perceptions of adult visitors who took guided tours at Onondaga Cave State Park in Leasburg, Missouri. An on-site survey was conducted on weekends, alternating between Saturdays and Sundays from May until October 2015. Crowding perceptions of White and Asian visitors were compared using an independent t-test, while a regression model examined the effects of different factors associated with perceived crowding. Results showed that Asian visitors felt more crowded on cave tours than Whites. Being Asian or White, along with tour satisfaction, were negatively associated with crowding perception. Implications for outdoor recreation management, both in theory and practice, were discussed.